2017
DOI: 10.1021/jacs.7b01010
|View full text |Cite
|
Sign up to set email alerts
|

Facile Construction of Metallo-supramolecular Poly(3-hexylthiophene)-block-Poly(ethylene oxide) Diblock Copolymers via Complementary Coordination and Their Self-Assembled Nanostructures

Abstract: Complementary coordination of two predesigned 2,2':6',2″-terpyridine-based ligands to a Zn ion led to the exclusive formation of a heteroleptic bis(terpyridine) complex under ambient conditions. This highly self-selective process was facilitated by 9-anthracenyl substituents at the 6,6″-positions of a terpyridine, which not only decelerated the formation rate of its homoleptic complex, but also provided π-stacking stabilization in the heteroleptic complex. Facile construction of metallo-supramolecular poly(3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 117 publications
1
71
0
Order By: Relevance
“…Controlling the nanoscale self-assembly of polymer materials is a key issue in various elds such as biomimetic materials [1][2][3][4][5] and exible electronics device science. [6][7][8][9][10] To achieve and improve control, both material synthesis and processing methodology have been developing synergistically, thereby providing molecular design and bottom-up approaches for the simple and precise control of nanostructures. The Langmuir-Blodgett (LB) technique is a notable example of nanoscale assembly using an air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the nanoscale self-assembly of polymer materials is a key issue in various elds such as biomimetic materials [1][2][3][4][5] and exible electronics device science. [6][7][8][9][10] To achieve and improve control, both material synthesis and processing methodology have been developing synergistically, thereby providing molecular design and bottom-up approaches for the simple and precise control of nanostructures. The Langmuir-Blodgett (LB) technique is a notable example of nanoscale assembly using an air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…16 Chan and co-workers also demonstrated that incorporation of both 2,6-dimethoxyphenyl, G , and anthracenyl, H , groups on to the terpy backbone can be used to selectively prepare the heteroligated complexes as a consequence of the favorable electronics of π-stacking in these cases. 17 Despite these and other 18 examples of arene-appended terpy ligands displaying favorable π–π interactions in the solid state, monoligated complexes, in the absence of additional ligands bearing extended π-systems, do not display parallel aryl substituents in the solid state 19 as a consequence of the central six-membered pyridine donor.…”
Section: Introductionmentioning
confidence: 98%
“…[29][30][31][32] For this method, the polymer units containing ligand moieties (macroligands) are rst designed and synthesized, and the tailored units are then held together through the coordination with metal ions. 12,[14][15][16][17][18][19][20][21][22][23][24]30 Among ligand groups, 2,2 0 :6 0 ,2 00 -terpyridine (Tpy) moiety is widely introduced into polymer building blocks for synthesizing macroligands, 12,[14][15][16][17][18][19][20][21][22][23][28][29][30][31][32] because it is able to form stable Tpy-M-Tpy (M, metal ion) complexes with a wide range of metal ions such as Ni(II), Fe(II), Cu(II), Co(II), Zn(II), Cd(II) and Ru(II), [29][30][31][32][33][34] making the formed metallosupramolecular polymers have a well-dened architecture. [15][16][17][18][19][20][21]<...>…”
Section: Introductionmentioning
confidence: 99%
“…12,[14][15][16][17][18][19][20][21][22][23][24]30 Among ligand groups, 2,2 0 :6 0 ,2 00 -terpyridine (Tpy) moiety is widely introduced into polymer building blocks for synthesizing macroligands, 12,[14][15][16][17][18][19][20][21][22][23][28][29][30][31][32] because it is able to form stable Tpy-M-Tpy (M, metal ion) complexes with a wide range of metal ions such as Ni(II), Fe(II), Cu(II), Co(II), Zn(II), Cd(II) and Ru(II), [29][30][31][32][33][34] making the formed metallosupramolecular polymers have a well-dened architecture. [15][16][17][18][19][20][21][22][23]30 Among complex species, Tpy-Ni(II)-Tpy and Tpy-Ru(II)-Tpy types exhibit good stability in water. 14 U. S. Schubert et al have investigated synthesis and coordination selfassembly of Tpy-containing polymers extensively and indepth.…”
Section: Introductionmentioning
confidence: 99%